Optimizing Protection Settings at PT PLN (PERSERO) UP2D Lampung through User-Centered Design and Model-View-Controller Architecture - Dewi Asiah Shofiana; Yunda Heningtyas; Siti Ayuni (Integra: Journal of Integrated Mathematics and Computer Science, 2026)
The rational basis for this research is the need to strengthen a Protection Management Information System in PT Perusahaan Listrik Negara (PLN) (Persero) UP2D Lampung so that it can implement monitoring and control systems or applications management protection settings quickly & accurately on electrical distribution system. Currently the company is using a manual process that uses Microsoft Excel, which is time-consuming and subject to human errors resulting in system reliability issues. In this paper, a new web-based system is developed based on the User-Centered Design (UCD) approach to provide an easy and friendly interface for field operators to handle filling process. Using the MVC (Model View Controller) architectural design pattern with CodeIgniter 4, it has structured and modularized code for easy maintenance and update. It automatically processes protection data, such as the Over Current Relay (OCR) and Ground Fault Relay (GFR) settings, its output to manager in a form easy to understand. The prototype was tested for usability via the User Equation Questionnaire (composed of Likert scale questions) with 19 respondents, allowing to determine a high usability score of 93.78% and validating the strong user satisfaction. The results of this study are expected to lead to the implementation of a reliable system with a user-friendly interface, ultimately enhancing the reliability of the electrical distribution system and speeding up responses to electrical issues in the Lampung region.